Analisis Hukum Bukti Elektronik sebagai Alat Bukti dalam Pemeriksaan Hukum Acara Perdata - Fauziah Lubis; Sonia Winda Khairani; Dimas Ardiansyah; Yusuf Zibron; Hafiz Alamsyah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to examine the evidentiary strength of electronic documents within the framework of civil procedural law. The issues addressed revolve around the legal legitimacy and effectiveness of electronic documents as means of evidence amid the ongoing digital transformation. The background of this research is grounded in the urgency for the judicial system to adapt to advancements in information technology. The methodology employed is normative juridical, using a statutory approach combined with an analysis of court decisions. The findings indicate that electronic documents possess evidentiary value if they comply with the principles of authentication and data integrity, although their practical implementation continues to face challenges within judicial proceedings.